IMPLANTAÇÃO DA CONSULTA DE PUERICULTURA NA ESTRATÉGIA SAÚDE DA FAMÍLIA - Chagas, Cristiane Brito da Luz (2017)
The childcare is conceived as a prior action in health services. In this context, the study aims to implement the nursing appointment in puericulture for children from zero to two years old in the Family Health Strategy. For specific objectives, this study considered to: create an instrument for nursing appointments in puericulture for children from zero to two years old and to form nursing professionals about the use of such instrument in the attendance in puericulture. To attend the first specific objective a qualitative research was done, through a focal group technique, with the participation of nurses from three groups the Family Heath Strategy from a center occidental municipality in Rio Grande do Sul State, during the months of May and August 2016. For the second, a formation was done, in December form the same year, with the same population, about the nutritious aspects of children from zero to two years old. From the data resultant and codified by the discourse analysis there are three thematic categories: integral evaluation of the children in a FHS; Children’s home visits and context recognition and autonomy, resoluteness and empowerment of the Nursing professional. In relation to the formation given, there are two categories: Doubts and longings that permeates the nurse performance in the implementation of the appointment of puericulture and the Difficulties that permeate the effectiveness of the care with the infant nourishment. It is concluded that the knowledge of nurses from FHS concerning the nutritional aspects that might be followed and oriented in the evaluation of the zero to two-year-old child, should be deepen pointing to the need of permanent formation in the thematic to improve the quality of the assistance given to the child and his family. Through the research done, the data found, the discussions brought by the focal groups, as well as the moments of formation referring to nutritional aspects, it was built an instrument for the appointment of nursing in puericulture in FHS. The use of adequate methodologies in the nursing appointments in puericulture favors the adequate accompaniment once they guarantee to the infantile health an integral and effective care in the actions of health prevention and promotion.